1987
DOI: 10.1042/bj2450325
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of the insulin-receptor kinase to thiol and oxidizing agents in the absence and presence of insulin

Abstract: The purified human placental insulin-receptor beta-subunit autophosphorylating activity was found to be inhibited, in a time- and concentration-dependent manner, by the specific thiol-alkylating agents N-ethylmaleimide and 5,5'-dithiobis-(2-nitrobenzoic acid). The insulin-receptor kinase was observed to be more sensitive to inhibition by N-ethylmaleimide in the presence [IC50 (concn, giving 50% inhibition) = 25 +/- 3 microM] than in the absence (IC50 = 73 +/- 6 microM) of insulin. Similarly, inhibition by 5,5'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 37 publications
4
25
1
Order By: Relevance
“…In addition, our studies provide a structural explanation for the widely observed stimulating effects of oxidants (28–32) and the effects of SH‐reactive reagents on the catalytic activity of the IRK (4345). It may be important in this context that HP production can also be induced among others by insulin (46).…”
Section: Discussionmentioning
confidence: 67%
“…In addition, our studies provide a structural explanation for the widely observed stimulating effects of oxidants (28–32) and the effects of SH‐reactive reagents on the catalytic activity of the IRK (4345). It may be important in this context that HP production can also be induced among others by insulin (46).…”
Section: Discussionmentioning
confidence: 67%
“…NEM inhibits autophosphorylation of the native insulin receptor (15)(16)(17)(18)(19), indicating that a free sulfhydryl group may be at or near the active site of the tyrosine kinase. It has been shown also that exposure of the insulin receptor to radioactive NEM results in incorporation of radioactivity into the /3 subunit (19).…”
Section: Resultsmentioning
confidence: 99%
“…The same laboratory (21) has shown that autophosphorylation is not inhibited when iodoacetamide is used to alkylate the receptor, suggesting that inhibition by NEM is due to steric interference.…”
Section: Methodsmentioning
confidence: 98%